Pilot Study of Voxel-Based Morphometric MRI Post-processing in Patients With Non-lesional Operculoinsular Epilepsy - Wang, Wei; Zhou, Qilin; Zhang, Xiating; Li, Liping; Xu, Cuiping; Piao, Yueshan; Wu, Siqi; Wang, Yajie; Du, Wei; Zhao, Zhilian; Lin, Yicong; Wang, Yuping (Frontiers in Neurology, 2020)
Objective: The aim of this study was to use voxel-based MRI post-processing in detection of subtle FCD in drug-resistant operculoinsular epilepsy patients with negative presurgical MRI, and by combining magnetoencephalography (MEG) to improve the localization of epileptogenic zone. Methods: Operculoinsular epilepsy patients with a negative presurgical MRI were included in this study. MRI postprocessing was performed using a Morphometric Analysis Program (MAP) on T1-weighted volumetric MRI. Clinical information including semiology, MEG, scalp electroencephalogram (EEG), intracranial EEG and surgical strategy was retrospectively reviewed. The pertinence of MAP-positive areas was confirmed by surgical outcome and pathology. Results: A total of 20 patients were diagnosed with operculoinsular epilepsy had nonlesional MRI during 2010-2018, of which 11 patients with resective surgeries were included. Four out of 11 patients had positive MAP results. The MAP positive rate was 36.4%. The positive regions were in insular in one patient and operculoinsular regions in three patients. Three of the four patients who were MAP-positive got seizure-free after successfully resect the MAP-positive and MEG-positive regions (the pathology results were FCD IIb in two patients and FCD IIa in one patient). Conclusions: MAP is a useful tool in detection the epileptogenic lesions in patients with MRI-negative operculoinsular epilepsy. Notably, in order to make a right surgical regime decision, MAP results should always be interpreted in the context of the patient’s anatomo-electroclinical presentation.